Quality characterization of artisanal and retail Turkish blossom honeys: Determination of physicochemical, microbiological, bioactive properties and aroma profile - Tornuk, Fatih; Karaman, Safa; Ozturk, Ismet; Toker, Omer Said; Tastemur, Bilge; Sagdic, Osman; Dogan, Mahmut; Kayacier, Ahmed (ELSEVIER, 2013)
In this study, physicochemical, microbiological and bioactive properties, major sugar and aroma profiles of total 20 artisanal (n = 10) and retail (n = 10) honey samples harvested in Turkey were determined. Physicochemical analyses showed that all honey samples were fresh and with good properties. In terms of sanitary conditions, all honey samples were considered as microbiologically safe. Total aerobic mesophilic and spore forming bacteria were detected in low counts while yeasts and molds were found in 15% and 20% of the honey samples, respectively. One retail honey sample did not meet the Codex Alimentarius standards in terms of its total glucose and fructose content while 75% of the honeys (60% and 90% of artisanal and retail honeys, respectively) had sucrose levels over the allowed limits (5%). There was a positive relationship between total phenolic content and DPPH scavenging activity of the honey samples. However, their antioxidant capacities were variable. Total 88 aroma compounds were detected by Gas Chromatography-Mass Spectrometry (GC-MS) analysis of the honeys. This study showed that there were not very sharp discriminations between retail and artisanal honeys when considering many of the parameters analyzed. Overall, it was confirmed that the quality of the analyzed honeys was good, which facilitates its national and international commercialization. (c) 2013 Published by Elsevier B.V.
Keywords: Turkish blossom honey; Physicochemical parameters; Microbiological quality; Aroma profile; Bioactive properties; VOLATILE COMPOUNDS; BOTANICAL ORIGIN; UNIFLORAL HONEYS; WATER ACTIVITY; ANTIOXIDANT; CLASSIFICATION; SUGARS; Agriculture